2019
DOI: 10.17159/0379-4350/2019/v72a9
|View full text |Cite
|
Sign up to set email alerts
|

Understanding How Chemistry Teachers Transform Stoichiometry Concepts at Secondary Level in Lesotho

Abstract: This qualitative study sought to investigate how secondary level chemistry teachers transform and represent subject matter knowledge (SMK). The study drew its theoretical framework from the notion of Pedagogical Content Knowledge (PCK) that foregrounds the teachers' ability to transform and represent SMK for students to understand the content presented. Seven qualified chemistry teachers participated in this study which used questionnaires, follow-up interviews, and lesson observations to collect data. The tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 20 publications
2
11
0
Order By: Relevance
“…The findings indicate that the taught lessons were predominantly teacher-centred and teacher-controlled. These results are consistent with previous studies such as Poti et al (2022) and Makhechane and Qhobela (2019). However, such teaching and learning environments may not effectively influence students' learning.…”
Section: Enactment Of Respiration Topic-specific Pedagogical Content ...supporting
confidence: 92%
See 1 more Smart Citation
“…The findings indicate that the taught lessons were predominantly teacher-centred and teacher-controlled. These results are consistent with previous studies such as Poti et al (2022) and Makhechane and Qhobela (2019). However, such teaching and learning environments may not effectively influence students' learning.…”
Section: Enactment Of Respiration Topic-specific Pedagogical Content ...supporting
confidence: 92%
“…The study found limited integration of TSPCK components (enactment of knowledge of conceptual teaching strategies). This result supports Makhechane and Qhobela (2019) who found that efforts to combine different teachers' knowledge areas were minimal. However, researchers have articulated the need for teachers to integrate the PCK components to successfully transform the content (Park & Chen, 2012).…”
Section: Enactment Of Respiration Topic-specific Pedagogical Content ...supporting
confidence: 86%
“…Lesson and classroom observation studies in poverty-stricken areas of South Africa, for example, those by Malcolm, Mavhunga, and Rollnick and Rollnick, Bennet, Rhemtula, Darsey, and Ndlovu, chronicle these constraints to promotion of conceptual stoichiometry SMK in teacher workshops and transfer to the classroom. Consistent with this, physical sciences teachers in developing countries, such as South Africa and its neighbor, Lesotho, have been shown to believe that pedagogical choices regarding stoichiometry are primarily to be dictated by examination guidelines rather than development of conceptual understanding. , …”
Section: Problem Statementmentioning
confidence: 88%
“…Consistent with this, physical sciences teachers in developing countries, such as South Africa and its neighbor, Lesotho, have been shown to believe that pedagogical choices regarding stoichiometry are primarily to be dictated by examination guidelines rather than development of conceptual understanding. 14,15 Such beliefs about the value of various types of SMK affect the feasibility of developing this SMK, 16 as do the quantity and quality of baseline SMK and ease and efficiency of development from that baseline. 4 Each of these factors is clearly contextually dependent.…”
Section: ■ Problem Statementmentioning
confidence: 99%
“…Numerous researches underscored that stoichiometry is one of the most challenging topics for students across educational levels (Aydin-Gunbatar & Kalender, 2019; Gulacar et al, 2019; Lausin, 2020; Scott, 2020; Shadreck & Enunuwe, 2018). Stoichiometric problem-solving requires a sound conceptual understanding of the quantitative relationships, mole ratio, balanced chemical equations, limiting and excess reagents, and theoretical yield (Dahsah & Coll, 2013;Makhechane & Qhobela, 2019). Apart from conceptual understanding, this is also related to students' metacognition (Fabelico, 2014;Ijirana & Supriadi, 2018;Syahmani, 2015).…”
Section: Introductionmentioning
confidence: 99%